Facing the pandemic aftermath: exploring depression and mental health service usage among first-year university students in southern Thailand - Pratummanee, Waluwan; Sangsuwan, Tharntip; Jatchavala, Chonnakarn; Sirirak, Thanitha (Frontiers in Psychiatry, 2025)
IntroductionDepression is a serious mental health concern in Thailand and a leading cause of psychological and physical impairment. Untreated depression can progress to more severe disorders. University students, in particular, must navigate developmental stages and pedagogical approaches to higher education curricula. Without appropriate intervention, depression in this population may progress to more severe depressive disorders. This study examined the prevalence, associated factors, and health service utilization patterns among first-year university students experiencing depression.MethodsThis cross-sectional study was conducted using an online survey among first-year students in southern Thailand three months into the semester, following the government’s approval to transition COVID-19 to an endemic disease in 2022. The survey collected data on demographic information, factors associated with depression, and mental health services access behavior. Descriptive statistics and logistic regression analysis were performed for data analysis.ResultsA total of 1,611 students participated in the study, 80.3% of whom were female, with an age range of 18–20 years (mean: 19.4, SD: 1.12). The prevalence of depression was 37.5%, with severity levels distributed as follows: moderate (21.4%), moderate to severe (11.4%), and severe (4.7%). Protective factors against depression included a grade point average (GPA) of 2.00–2.49 or 4.00, attending private schools, being single, having close relationships with friends and partners, and following a healthy diet, and moderate to high self-confidence was associated with an increased likelihood of depression. Most participants did not consider seeing a psychiatrist troublesome or embarrassing, either for themselves or others. Moreover, they did not perceive the process of accessing mental health services in Thailand as complicated. However, they did not tend to seek mental health information online or from friends, teachers, parents or guardians.DiscussionThe prevalence of depression among participants from southern universities in Thailand that are members of the ASEAN University Network–Health Promotion Network during the first three months of the academic year was 37.5%. Protective and risk factors included GPA, high school type, presence of a partner, relationships with friends and partners, eating habits, and self-confidence. Although students generally perceived mental health services as accessible, many were unaware of university-provided services and did not seek mental health information from close contacts such as parents, guardians, teachers, or friends.